Application of Sharia Principles and Consumer Interest in Sharia Hotels - Ulum, Miftachul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of this study was to find out the application of sharia principles and consumer interest in choosing the Walisongo Syariah Hotel Surabaya. Multiple regression analysis method with 3 variables namely Sharia Label (X1), Application of Sharia Principles (X2) and Consumer Interest (Y) involving 50 respondents. The results of the study obtained that the application of sharia principles has been carried out in operational activities at the Walisongo Syariah Hotel, Surabaya. There is a significant relationship between sharia labels and consumer interest in the Walisongo Syariah Hotel Surabaya. The application of sharia principles is significant at 0.941 which greatly influences consumer interest in using the Walisongo Syariah Hotel Surabaya. The better the application of sharia principles, the higher the interest of consumers to use sharia hotels as accommodation services